A geoestatística como ferramenta de estudo da batimetria na vertente continental portuguesa - Machado, Pedro Bordalo; sousa, António Jorge (Finisterra, 2003)
GEOSTATISTICS AS A TOOL FOR THE STUDY OF BATHYMETRY ON THE PORTUGUESE CONTINENTAL SLOPE. The increasing interest on deep-water resources by the commercial fishing fleet during the last 20 years led the Fisheries Research National Institute (presently INIAP-IPIMAR) to conduct seafloor topography studies, which aimed the identification of potential fishing grounds for deep-water species in the Portuguese continental slope.The present study lies in the scope of the above topography studies. The spatial variability of the seafloor depth from a particular area of the Portuguese continental slope off Figueira da Foz with about 665 sq. m. was investigated. A geostatistical analysis comprising spatial continuity, several estimation methods and its uncertainty was conducted. The sequential gaussian simulation method was applied to evaluate estimation values uncertainty.Residual kriging yielded the lower estimation errors. The higher uncertainty observed in the estimation results obtained by Ordinary Kriging suggests that the geostatistic model to be adopted for the study area should be non-stationary. However its implementation is more straightforward since it has less requirements. Based on the estimation and simulation results two digital maps were constructed for the study area, one on the bathymetry and the other on the trawl fishing uncertainty.